Propuesta de estrategias para la disminución del indicador de agua no contabilizada (ANC) y control de fugas – cercado de la ciudad de Chiclayo - Cruzate Cabrejos, Roy Manuel (2019)
In the department of Lambayeque, the production of drinking water demands high maintenance costs for the EPS, either in its collection, purification and subsequent distribution. The relevant costs are: investment in infrastructure, personnel costs, operational costs such as: electricity, chemicals, misuse of this, etc.; administrative costs, system management costs, and costs that are reversed by paying the service provided by users. In EPSEL S.A., there is a difference between the volumes of water produced and those billed, reaching the average of 43.56% and 46% overall of Non-Billed Water (ANF). These are the statistics from 2016 and 2017 respectively. Therefore, efforts should be prioritized to reduce these differences that have a negative economic relevance in the management of the company. In this context, the present approach to address these issues will be called execution of the study “Design of strategies for the decrease of uncontrolled water indicator (ANC) and leak control -closed to the city of Chiclayo (sector VII)”.This aims to propose a program that addresses the social axis seeking diligent users and the management axis involving the EPS being the main responsible. This is interested with the sole purpose of reducing the water not accounted for in sector VII of the city of Chiclayo. Maintaining acceptable levels of water loss is a challenge for the sanitation management companies, especially in a global scenario where water is an increasingly scarce resource. The proposed consists of the following parts: informative data, background, sectorization, objectives, description of the alternative, justification, main analysis criteria, strategies to be used, expected results and means to achieve it.